2020
DOI: 10.1186/s12882-020-02188-8
|View full text |Cite
|
Sign up to set email alerts
|

The real-world effectiveness of sucroferric oxyhydroxide in European hemodialysis patients: a 1-year retrospective database analysis

Abstract: Background The iron-based phosphate binder (PB), sucroferric oxyhydroxide (SFOH), demonstrated its effectiveness for lowering serum phosphate levels, with low daily pill burden, in clinical trials of dialysis patients with hyperphosphatemia. This retrospective database analysis evaluated the real-world effectiveness of SFOH for controlling serum phosphate in European hemodialysis patients. Methods De-identified patient data were extracted from a clinical database (EuCliD®) for adult hemodialysis patients from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Retrospective observational studies of both hemodialysis and peritoneal patients have also reported small but significant initial increases in ferritin and TSAT during treatment with SO [33][34][35][36][41][42][43]. The findings are consistent with the minimal iron absorption from SO reported in the Phase 3 trial and its extension [30].…”
Section: Impact Of So Therapy On Iron Parameters and Anti-anemia Medi...supporting
confidence: 53%
See 4 more Smart Citations
“…Retrospective observational studies of both hemodialysis and peritoneal patients have also reported small but significant initial increases in ferritin and TSAT during treatment with SO [33][34][35][36][41][42][43]. The findings are consistent with the minimal iron absorption from SO reported in the Phase 3 trial and its extension [30].…”
Section: Impact Of So Therapy On Iron Parameters and Anti-anemia Medi...supporting
confidence: 53%
“…A retrospective study evaluated the real-world effectiveness of SO in European hemodialysis patients, utilizing data from the EuCliD ® database to analyze a cohort of hemodialysis patients from five European countries who were prescribed SO for up to 1 year [ 42 ]. Serum phosphorus and PB pill burden of the overall cohort ( n = 1,096) were compared between a 3-month baseline period prior to SO initiation and four quarterly periods of SO therapy (Q1 − Q4).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations